Las estrategias comunicacionales y la transportación masiva - Ponce Chóez, María Esther (2016)
The initiative of the research project arises from the problem that exists in mass transit Metrovía used in Guayaquil, since in recent months has been evidenced in media, such as RTS, channel that broadcast on 6 November 2015 in the morning news program La Noticia, a story where the excesses that cause students of educational institutions are observed in addition to the improper entry to the stops, actions that reflect the bad behavior that young people, mostly students by accessing this means transport incorrectly risking their lives to enter the busway to avoid paying the ticket, as well as misuse of recharging machines whose function is to accredit balance cards that allow entry. This series of actions that prevent quick service are caused by system users, mostly young students who exercise wrong attitudes, making this behavior on a point of analysis, because there is no logic in harm or lash out at a service that works for the benefit of many; being felt by these actions of the society lacks culture and information, which in many cases coupled with the lack of knowledge of how to use a service bring the effect of delaying it, resulting harmed citizens…..